HERBAL TOOTH GEL FOR THE MANAGEMENT OF GINGIVAL BLEEDING AND TOOTHACHE (Journal of Pharmaceutical Negative Results, 2023)
Periodontal disorders are caused by gum and bone infections and inflammation. Gingivitis is a bacterial infection that inflames the gingiva. In advanced periodontal disease, many patients need tooth extractions or other surgical operations, which can be lethal. Spilanthes acmella relieves toothaches and induces salivation. Green tea's polyphenolic catechins combat plaque and bacteria. This study intends to produce herbal tooth gel for managing gingival bleeding and toothache. This herbal gel contains Spilanthes acmella, Green Tea and clove oil. Decoction extracts Spilanthes acmella with green tea. The gel basis was made by combining carbomer 940, PEG400, TEA, sorbitol, and clove oil. Macroscopic and microscopic examinations were performed. Passing formulations were examined further to reach the necessary gel composition. All tests and trials for various parameters showed that the final formulation maintained a stable pH over 3 months, suggesting that clove oil performed its role as a natural preservative with satisfactory results, preventing microbial growth, decomposition, and incompatibilities among the components. The compositions retained viscosity and stability over 3 months, indicating that their constituents were compatible. It could be used as a dental gel for toothache and gingival bleeding.